The Analysis on the Potential Development and Employment Opportunities from the Sub-Sector of Creative Economy in Indonesia - Amelia, Rizky Nur (Jurnal Ilmiah Mahasiswa FEB, 2016)
The development of population will come hand in hand with the need of workforce requirements. This may cause serious problem if the increased population is not in line with job vacancy. Creative economy as the part of economy which focuses in creating products and service through creativity and intellectual may be the solution of the impending problem on job provision. Therefore, it is important to see whether creative economy can provide the solution. This study uses quantitative method to see the relationship of economic growth and work vacancy. To analyze the relationship elasticity model is employed by comparing the ratio of employment growth and national revenue. Based on the elasticity analysis results, the score of the sectors are low or under 1 point. The largest result are gained by research and development 0,38%. Although the elasticity scores of the fashion 0,12%, culinary 0,02% and craft 0,25% are low, in reality, these three sub sector have successfully generated large number of employment which make them featured sectors to alleviate unemployment in Indonesia.Â  Keyword : Creative Economy, Unemployment, Elasticity